2023
DOI: 10.1021/acs.estlett.3c00124
|View full text |Cite
|
Sign up to set email alerts
|

The Adverse Effect of Concentration Polarization on Ion–Ion Selectivity in Nanofiltration

Abstract: While the detrimental effect of concentration polarization (CP) on water flux and solute rejection in pressure-driven membrane processes has been extensively explored, the impact of CP on the selectivity between solutes in these processes has been somewhat overlooked. Considering the growing interest in solute–solute selectivity, in this study, we explored the effect of CP on ion–ion selectivity in nanofiltration (NF) membranes. We first show and discuss the “reversed” observed rejection trend of monovalent ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Compared with the modified commercial and advanced manufactured NF membranes, the (PEI-TMC)-NH 2 membrane displayed a high water permeance and separation factor (Li + /Mg 2+ ) (Figure 3h, Table S4), 44−49 while the (PEI-TMC)-COOH membrane displayed a high water permeance and separation factor (Cl − / SO 4 2− ) (Figure 3h, Table S5). 25,50−55 We noticed that Ophir et al 65 recently reported the impacts of concentration polarization on the ion−ion selectivity of polyamide membranes. Therefore, the reported apparent separation factors in this study, which are more convenient for evaluating membrane separation performance in industrial applications, might differ from the real separation factors after consideration of concentration polarization.…”
Section: Ion−ion Selectivity and Mechanism Of The (Pei-tmc)-nh 2 And ...mentioning
confidence: 97%
“…Compared with the modified commercial and advanced manufactured NF membranes, the (PEI-TMC)-NH 2 membrane displayed a high water permeance and separation factor (Li + /Mg 2+ ) (Figure 3h, Table S4), 44−49 while the (PEI-TMC)-COOH membrane displayed a high water permeance and separation factor (Cl − / SO 4 2− ) (Figure 3h, Table S5). 25,50−55 We noticed that Ophir et al 65 recently reported the impacts of concentration polarization on the ion−ion selectivity of polyamide membranes. Therefore, the reported apparent separation factors in this study, which are more convenient for evaluating membrane separation performance in industrial applications, might differ from the real separation factors after consideration of concentration polarization.…”
Section: Ion−ion Selectivity and Mechanism Of The (Pei-tmc)-nh 2 And ...mentioning
confidence: 97%